2020
DOI: 10.1177/0194599820933255
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Screening of Adults With Postlingual Hearing Loss: A Systematic Review

Abstract: Objective To systematically review the evidence for the use of cognitive screening tools for adults with postlingual hearing loss. Data Sources PubMed, Embase, Scopus, PsycINFO (EBSCO), CINAHL (EBSCO), and CENTRAL (Cochrane Library) electronic databases were searched from inception until October 4, 2018. Review Methods Articles were reviewed for inclusion by 2 independent reviewers. The references of included articles were hand-searched for additional relevant articles. Data were extracted by 2 independent ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 94 publications
0
18
0
Order By: Relevance
“…A significant proportion of studies exploring cognition used screening measures, which have noted limitations as the primary form of assessment. Raymond et al (2020) systematic review of cognitive screening with adults with post-lingual hearing loss confirmed the frequent use of screening assessments such as the MMSE and the Montreal Cognitive Assessment (MoCA), both of which are reliant on auditory components. The authors note that based on the available evidence, these auditory components may have a deleterious effect on scores for adults with hearing loss.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A significant proportion of studies exploring cognition used screening measures, which have noted limitations as the primary form of assessment. Raymond et al (2020) systematic review of cognitive screening with adults with post-lingual hearing loss confirmed the frequent use of screening assessments such as the MMSE and the Montreal Cognitive Assessment (MoCA), both of which are reliant on auditory components. The authors note that based on the available evidence, these auditory components may have a deleterious effect on scores for adults with hearing loss.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, poor performance may be an indication of poor cognition, poor audibility for instruction, or increased effort for listening, which is known to impact working memory and recall ( Wayne et al, 2016 ). Adaptations to screening measures to adjust for auditory components have also proven problematic, as the removal and modification of items can directly influence the pass/fail status (sensitivity) ( Parada et al, 2020 ) and these modifications may not yet have been formally validated ( Dawes et al, 2019 ; Raymond et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a statistical survey of otolaryngologists and audiologists showed that the rate of cognitive function assessment for hearing loss patients was only 21.21% (Raymond et al, 2020 ), which indicates that the practice of cognitive assessment of high-risk groups, such as patients with ARHL, in clinical practice is not yet universal. This could be because the relationship between the two has not yet been popularized and further due to the lack of objective quantitative indicators with high sensitivity and specificity (Panza et al, 2015 ; Raymond et al, 2021 ). The development of electrophysiological technologies, such as EEG and MRI, provides the opportunity to achieve this goal.…”
Section: Discussionmentioning
confidence: 99%
“…[54][55][56][57] In the most frequently used neurocognitive screening batteries, the MMSE and the MoCA (Montreal Cognitive Assessment), 7 versus 10 out of 30 points depend on auditory presented stimuli, respectively. 47,48,58,59 This is also true for the DemTect, which is highly sensitive to (mild cognitive impairment) MCI detection and quite popular in Germany. 60 It consists of 5 subtests covering attention, (delayed) recall, transcoding of numbers, and language abilities and it has been validated in 363 patients with age-dependent cut-off scores.…”
Section: Cognitive Testing In Subjects With Hearing Lossmentioning
confidence: 91%
“…After detailed full-text analysis, 21 articles dealing with the impact of hearing loss on cognitive testing were identified. One article was not available in full-text version, 46 two publications were reviews, 47,48 one was a review and a meta-analysis 49 and two were study protocols. 50,51 15 studies including participants of different age groups and hearing abilities were analyzed in detail (see Table 2).…”
Section: Impact Of Hearing Loss On Geriatric Assessments In Generalmentioning
confidence: 99%